A randomized, double‐blind, single‐dose, three‐arm, parallel group study to determine pharmacokinetic similarity of ABP 959 and eculizumab (Soliris®) in healthy male subjects. (27th April 2020) - Chow, Vincent; Pan, Jean; Chien, David; Mytych, Daniel T.; Hanes, Vladimir
Abstract: Objectives: ABP 959 is a proposed biosimilar to eculizumab, a monoclonal antibody targeting the human C5 complement protein. The objective of this randomized, double‐blind, three‐arm, study was to demonstrate pharmacokinetic (PK) and pharmacodynamic (PD) similarity of ABP 959 relative to the eculizumab reference product (RP) in healthy adult male subjects. Methods: Eligible subjects aged 18‐45 years were randomized to receive a 300‐mg IV infusion of ABP 959, or FDA‐licensed eculizumab (eculizumab US), or EU‐authorized eculizumab (eculizumab EU). Primary PK endpoint was area under the total serum concentration‐time curve from 0 to infinity (AUC0−∞ ); primary PD endpoint was area between the effect curve (ABEC) of CH50‐time data. Results: The geometric mean of PK and PD parameters were similar between ABP 959 versus eculizumab US and eculizumab EU; PK and PD similarity was established based on 90% confidence intervals of the geometric mean ratio being within prespecified equivalence margin of 0.8 and 1.25. The incidence of treatment‐emergent adverse events was similar across groups. The incidence of binding anti‐drug antibodies was similar across treatments; no subjects developed neutralizing antibodies. Conclusions: This study demonstrated PK and PD similarity of ABP 959 to eculizumab RP; safety and immunogenicity profiles were also similar.